2011
DOI: 10.2989/1814232x.2011.637616
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic behaviour of southern right whales in relation to numbers of whales present in Walker Bay, South Africa

Abstract: Estimating numbers of whales present in an area from recorded call rates could be a useful conservation tool. We recorded southern right whale Eubalaena australis vocalisations and presence in Walker Bay on the south coast of South Africa. In all, 45 sessions with synchronous acoustic and visual data were analysed to determine call rates directly (overall call rate, OCR) and in relation to the number of whales sighted (call rate per whale, CPW) and number of groups sighted (call rate per group, CPG).The OCRs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Over the past decade, extensive effort has been made to understand the vocal behavior of the highly endangered North Atlantic right whale Eubalaena glacialis -NARW Parks et al, 2011;Mussoline et al, 2012;Matthews et al, 2014;Bort et al, 2015). In contrast, since the first repertoire descriptions of southern right whales' (Eubalaena australis -SRW) by Clark (1982Clark ( , 1983 little attention has been given to this species' acoustic ecology in the Southwest Atlantic (Hofmeyr-Juritz and Best, 2011;Tellechea and Norbis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, extensive effort has been made to understand the vocal behavior of the highly endangered North Atlantic right whale Eubalaena glacialis -NARW Parks et al, 2011;Mussoline et al, 2012;Matthews et al, 2014;Bort et al, 2015). In contrast, since the first repertoire descriptions of southern right whales' (Eubalaena australis -SRW) by Clark (1982Clark ( , 1983 little attention has been given to this species' acoustic ecology in the Southwest Atlantic (Hofmeyr-Juritz and Best, 2011;Tellechea and Norbis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Twelve call types of SRWs have been defined to date in South African waters (Hofmeyr‐Juritz, 2010; Hofmeyr‐Juritz & Best, 2011). Additionally, SRWs produce a short, distinctive broadband explosive sound termed the gunshot sound (Clark, 1983; Hofmeyr‐Juritz & Best, 2011; Webster et al, 2016). The gunshot sound is termed so “because of its acoustic similarity to the sound of a rifle being fired” (Parks et al, 2005).…”
Section: Figurementioning
confidence: 99%
“…
However, Best (2006) and Mate et al (2011) showed that the coastal waters of the South African west coast are also used as an austral spring/summer feeding ground by the portion of the population that remains there year-round.Seasonal acoustic occurrence of SRWs in South African waters is currently based on short-term shallow coastal (adjacent to the coast and within the 100 m isobath) research (Figure 1; Hofmeyr-Juritz, 2010; Vinding-Petersen,-2016). An expansion of such acoustic work to more offshore waters (Figure 1) and more long-term programs is useful for a more comprehensive understanding of the species' seasonal occurrence patterns.Twelve call types of SRWs have been defined to date in South African waters (Hofmeyr-Juritz, 2010;Hofmeyr-Juritz & Best, 2011). Additionally, SRWs produce a short, distinctive broadband explosive sound termed the gunshot sound (Clark, 1983;Hofmeyr-Juritz & Best, 2011;Webster et al, 2016).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although clearly advantageous, the application of PAM for research and monitoring of cetacean species in African waters has lagged behind other more affluent regions. There have been some recent advances in this field (Hofmeyr-Juritz and Best, 2011;Gridley et al, 2012;Gridley et al, 2014;Gridley et al, 2015), however, basic data on the call repertoire and vocal characteristics of most cetacean species encountered in southern Africa are still missing (Best, 2007;Elwen et al, 2011). Such data are necessary for the implementation of successful PAM programs.…”
Section: Introductionmentioning
confidence: 99%